Petunjuk Teknis Penyusunan Laporan Keuangan Bagi Pengelola Bumdes di Desa Wotanmas Jedong, Kecamatan Ngoro, Kabupaten Mojokerto - Azizah Fitriani; Saiful Anam (Lembaga Pengembangan Kinerja Dosen, 2025)
Accounting records are an important part of every BUMDes, but many still do it manually and do not have financial reports. To overcome this, the community service team plans to provide support to Wotanmas Jedong Village through financial literacy training and accounting methods. This training is intended for BUMDes administrators and village treasurers, with routine assistance in each business unit. Evaluation findings show that participants' understanding is getting better, and they can now identify assets and organize financial data more neatly. In order to increase the effectiveness of the program, it is recommended to use an integrated accounting application and additional training related to asset management and accounting technology. Thus, this training not only develops the skills of BUMDes managers, but also ensures transparency and accountability in financial operations in line with applicable accounting standards.